The Cultivation of Social Attitudes through Civic Education Learning in the Pandemic Era as an Effort to Build Students' Social Skills - Damanhuri Damanhuri; Ria Yuni Lestari (Universitas Sultan Ageng Tirtayasa, 2021)
Indonesia and other countries in the world are being hit by a very extraordinary health crisis that is Covid-19. Covid-19 also has an impact on the implementation of learning in universities, implementation of lectures using the online method. Citizenship Education courses that teach about norm values are a bit difficult to implement online because they cannot directly observe student attitudes which are reflected in the course content. Inculcating social attitudes in learning during this pandemic is very important. Because it is expected that students have social awareness of the current situation. The importance of social attitudes in learning so that students have social skills so that they are able to establish good cooperation to achieve the learning object of citizenship education. Social Skill and social attitudes are one of the indicators in realizing the smart and good citizen goal of Civic education. Having a social attitude makes students more sensitive to problems that occur in the surrounding environment and can participate in finding solutions to problems that exist in the community. The purpose of this study was to find out how to instill Social Attitudes through Citizenship Education Learning in the Covid-19 Pandemic Era as an Effort in Formation of Student Social skills. This study uses a descriptive qualitative approach with data collection observations, documentation and interviews. The results of the study show that the practice of social skills through Civic Education learning in this Pandemic era is carried out by habituation. Social attitudes that are instilled are honesty, discipline, responsibility, polite, caring, and confident. Habituation carried out in the learning process can take place through demonstrations and agreements made between students and lecturers together in the classroom. Inculcating social skills in learning is greatly assisted by online learning platforms such as LMS and social media. Researchers’ recommendation is that further research can develop the acquisition of other skills in Citizenship Education learning.